Internalized stigma in people with severe mental illness in rural China. (February 2018) - Ran, Mao-Sheng; Zhang, Tian-Ming; Wong, Irene Yin-Ling; Yang, Xin; Liu, Chang-Cheng; Liu, Bo; Luo, Wei; Kuang, Wei-Hong; Thornicroft, Graham; Chan, Cecilia Lai-Wan
Background: It is unknown whether there are differences in self-stigma among persons with different types of severe mental illness (SMI) in rural communities. Aim: This study was to examine the differences of self-stigma and its correlates in persons with schizophrenia, major depressive disorder or bipolar disorder in a rural community in China. Methods: A total of 453 persons with schizophrenia, major depressive disorder or bipolar disorder in a rural community participated in the study. The Internalized Stigma of Mental Illness (ISMI) was used to measure self-stigma. The t -test and analyses of variance (ANOVA) were used to examine the differences in mean scores of ISMI and subscales among the three diagnoses. Logistic regression was used to explore the contributing factors to the level of self-stigma among the three groups. Results: Self-stigma was moderate and severe with 94.7% of the total sample. Persons with schizophrenia had significantly higher mean scores of total ISMI, alienation and discrimination experience than those with bipolar disorders. Lower family income was significantly associated with higher levels of self-stigma in persons with schizophrenia and major depressive disorder. Factors predicting the level of self-stigma among the three groups were various. Conclusion: Self-stigma is common and severe in persons with schizophrenia, major depressive disorder and bipolar disorder, especially those with lower income status in rural community in China. Persons with schizophrenia may have higher levels of self-stigma than those with bipolar disorder. Individual-level interventions should be developed to reduce self-stigma among persons with SMI in Chinese rural communities.